The Use of Gut Microbial Modulation Strategies as Interventional Strategies for Ageing - Ruqaiyyah Siddiqui; Mohammad Ridwane Mungroo; Ahmad M. Alharbi; Hasan Alfahemi; Naveed Ahmed Khan (Microorganisms, 2022)
Gut microbial composition codevelops with the host from birth and is influenced by several factors, including drug use, radiation, psychological stress, dietary changes and physical stress. Importantly, gut microbial dysbiosis has been clearly associated with several diseases, including cancer, rheumatoid arthritis and Clostridium difficile-associated diarrhoea, and is known to affect human health and performance. Herein, we discuss that a shift in the gut microbiota with age and reversal of age-related modulation of the gut microbiota could be a major contributor to the incidence of numerous age-related diseases or overall human performance. In addition, it is suggested that the gut microbiome of long-lived animals such as reptiles should be investigated for their unique properties and contribution to the potent defense system of these species could be extrapolated for the benefit of human health. A range of techniques can be used to modulate the gut microbiota to have higher abundance of “beneficial” microbes that have been linked with health and longevity.